(untitled) (Journal of Preventive and Social Medicine, 2022)
Background: Chronic kidney disease is a steadily growing health problem. Malnutrition is common in this irreversible state of kidney failure. The CKD along with malnutrition adversely affect the HRQOL of the patients. This study was conducted to assess the association between nutritional status and HRQOL of CKD patients. Methods: This cross-sectional study was conducted among 220 CKD patients at Gonoshasthaya Dialysis Centre in Dhaka of Bangladesh during the period from July 2019 to June 2020. Data were collected purposively by using a semi-structured questionnaire with face to face interview, physical examinations and review of medical records. Results: In this study, majority of the patients were male (67.7%) and mean (±SD) age was 47.59±12.51 years. The patients were higher in proportion (60.0%) in stage 5. Mean (±SD) duration of CKD was 3.8 (±1.83) years. Based on SGA score, majority of the patients (81.8%) were mild to moderately malnourished while 5.5% were severely malnourished. Overall mean (±SD) score of HRQOL was 47.07 (±14.89). The score was higher (53.84±13.60) in KDCS followed by MCS (45.99±21.06) and PCS (41.35±14.92). Mean (±SD) score of HRQOL was 33.27±9.80, 45.67±14.26 and 61.96±9.16 in severely malnourished, mild to moderately malnourished and well-nourished patients respectively (F = 24.191, p < .001). Correlation between mean score of HRQOL and SGA score was positively significant (r= .709, p<.001). Age, income, family member, duration of CKD, hemoglobin, serum albumin and SGA score together accounted for 65.6% variability of HRQOL score (R2 = 0.656, adjusted R2 = 0.645, (F= 57.829, p <.001) with the SGA score recording a higher beta value (beta = 0.474, p <.001). Conclusion: The study found, most of the patients were malnourished with a low level of HRQOL score. Correlation between the mean score of HRQOL and SGA score was significant and strongly positive. JOPSOM 2021; 40(2): 44-51